SYNTAX Score 2020 Risk Estimates Between PCI and CABG in Coronary Artery Disease : A Descriptive Study - Alysa Masytha Masyhudi; Sanggap Indra Sitompul; Karina Yesika Manalu; Refiansyah Tri Anggoro; Yusuf Galenta (Jurnal Kardiologi Indonesia, 2026)
Background: The SYNTAX Score 2020 is a validated tool that combines anatomical and clinical parameters to estimate long-term outcomes in CAD and guide revascularization decisions between PCI and CABG. Although its components are well defined, further studies are needed to clarify how clinical variables influence risk predictions in diverse populations, including Indonesia. Methods: This cross-sectional study enrolled 115 patients with angiographically confirmed CAD at dr. Doris Sylvanus Regional General Hospital, Palangka Raya, Indonesia, between January and June 2025. The SYNTAX Score 2020 and anatomical SYNTAX Score I were calculated using the official application. Statistical analyses included bivariate non-parametric tests, Spearman correlations, and multivariate linear regression to identify independent clinical determinants of the SYNTAX Score 2020–predicted 10-year mortality and 5-year MACE following PCI and CABG. Results: PVD and DM were strongly associated with a higher SYNTAX Score 2020–predicted 5-year MACE and 10-year mortality after both PCI and CABG, with a stepwise increase in risk from no DM to insulin-treated DM. LMCAD was associated with a higher CABG-predicted risk than 3VD, whereas smoking was not associated with predicted outcomes. Age and SYNTAX Score I were positively correlated with all risk estimates, whereas CrCl and LVEF were inversely correlated. In the multivariate models, age, PVD, DM, and lower LVEF remained independent predictors for both strategies; SYNTAX Score I remained significant only for PCI, and CrCl was no longer independently associated with risk. Conclusion: Age was the main independent predictor of a higher SYNTAX Score 2020 that predicted long-term risk, followed by PVD and diabetes (highest in insulin-treated DM). Higher LVEF was protective, and left main disease carried a higher predicted risk than three-vessel disease.